SOSIALISASI PEMBUATAN ECO-ENZYME SEBAGAI PUPUK CAIR DAN DESINFEKTAN ALAMI DI DESA ADAT GUWANG KABUPATEN GIANYAR - A.A.A Made Cahaya Wardani; I Nyoman Suta Widnyana; Cokorda Putra; Ida Ayu Putu Sri Mahapatni; Made Novia Indriani (JURNAL SEWAKA BHAKTI, 2023)
During religious ceremonies, the presence of waste tends to increase, dominated by organic and household waste. The composition of organic waste is mostly caused by ceremonial waste from a series of leaves or fruits. The same thing happened in the Guwang Traditional Village, Gianyar Regency. This activity aims to find out the existence of waste and waste banks in the Guwang Sukawati Traditional Village and to socialize the manufacture of eco-enzymes, through several stages including conveying the benefits of eco-enzymes, demonstrating the making of eco-enzymes, to the stage of module distribution and evaluation involving local community. The socialization of making eco enzyme was highly appreciated and enthusiastically welcomed by the pekaseh and members of the Babakan subak in the Guwang Traditional Village, this is because the farmers can directly feel and use it. This socialization is also very right on target because it is directly given to farmers in the village and is expected to open their horizons in managing organic waste and using environmentally friendly fertilizers.